Dermatology - Braun-Falco, Otto; Plewig, Gerd; Wolff, Helmut H.; Burgdorf, Walter H. C. (Springer Berlin Heidelberg, 2000)
The "skin" classic in a completely updated new edition. Sure to prove essential reading for all practitioners in this fast-moving medical discipline, the new 3rd edition of Braun-Falco’s Dermatology covers classical dermatology and many related fields, providing a wealth of information on pathophysiology, clinical features, diagnostic methods, and differential diagnostic considerations, as well as the latest therapeutic approaches. Numerous new chapters covering diagnostic approaches (dermatopathology, dermatoscopy and sonography), as well as aging skin, sports dermatology and aesthetic therapy. Almost 1,000 superb photos and diagrams help the reader become acquainted with the numerous facets of dermatological diseases. A must for every doctor confronted with dermatological problems. Let over 100 experts help you in your daily practice!